Dinâmica dos escoamentos na modelagem da produção de sedimentos em uma pequena bacia rural - Barros, Claudia Alessandra Peixoto de (2016)
The models based on spatially distributed processes describe erosion and sediment yield using a physical approach of the mechanisms. In general, these models require high quality input data, description of the landscape, insertion of the physical processes involved, among others. Thus, it is not uncommon to find models that due to some operational difficulty do not fit well in the natural processes. Therefore, the objective of this study was to understand the hydrological and sedimentological dynamics of the Arvorezinha/RS experimental catchment in order to set the constraints of mathematical modeling that generate the overestimation in modeling the suspended sediment concentration (SSC) and sediment yield (SY). The study took place in the Arvorezinha experimental catchment, located in southern Brazil, which possesses a total drainage area of 1.23km2. Along with hidrossedimentological monitoring, there was an insertion of solute analysis through dissolved silicon (Sid) and particulate during and between precipitation events. This was carried out to understand the hydrological behavior of the catchment as well as assist in flow separation. The mathematical modelling of the erosive process was done with the LISEM model for the nine events monitored with Sid. In addition, we conducted an analysis of extreme events and variables responses, especially for SY, between 2010 and 2015. The years of 2014 and 2015 were the wettest since 2010, which had around 2.500mm of rain. The events monitored with Sid led us to conclude that the sub-surface flows have the biggest contribution during the event of precipitation, especially in events that take place in autumn-winter and low-average magnitude. Furthermore, it was possible to observe the effect of dilution that occurs during the events, that is, as liquid discharge increases, the concentration of Sid reduces. This is reflected in the suspended sediment concentration, because, as the event occurs, the SSC resulting from the surface flow will be diluted in the subsurface flow. Because, according to the present study, these water movements with lower speeds have a very important role in the hydrograph (it was higher than or close to 50% of the total volume). Therefore, the modeling of the erosive process is significantly influenced by the contribution of the slow flows (subsurface and groundwater flow), given that the model simulates the quick flow (superficial). In this way, LISEM model usage in areas with lower flow speeds can be limited; consequently, a greater level of care is required when concluding on the use of the model and their capacity to represent the hidrossedimentological processes.